Determinación de resistencia antibiótica de Salmonella spp., a partir de carne de pollos comercializados informalmente en el cantón Latacunga. - Villarreal Bastidas, Jorge Elian (2022)
Salmonella spp., is the main bacterial genus responsible for causing foodborne diseases worldwide, since it is present in animal and vegetable origin products, being one the most infection important means with chicken meat. Therefore, the aim this study was to determine the antibiotic resistance of Salmonella spp., from chicken meat informally marketed in the Latacunga canton, it was made through an observational study, which required the soup enrichment into Lactose broth and Tetrathionate and its seeding into selective Bismuth Sulfite agar to isolate and identify the enterobacteria species and genus, through the biochemical tests use and the Gram stain technique, ending with the antibiogram performance by the diffusion method into Mueller agar. Hinton II, proposed by Kirby Bauer. It was identified six clinically important Enterobacteriaceae, it presents in all the (n=30) samples. The prevalence of Salmonella spp. is 10%. The isolates Salmonella spp., show resistance to 9 of 11 used antibiotics, being the antimicrobial with tetracycline, it was the most resistance cases evidenced, unlike florfenicol, since all isolates are sensitive to the action this drug. Most isolates of Salmonella spp. in the study, they are multi-resistant, for this reason, which it is essential to reinforce the control measures this pathogen, to avoid the development and dispersion this bacteria type, given that antimicrobials are losing their effectiveness, either due to improper use or by the bacteria´s capacity to adapt, which, in turn, it is fostered by poor handling and hygiene practices, when producing or handling food for human consumption.